Africa's Got Work to Do : Employment Prospects in the New Century - Fox, Louise (IMF Working Papers; Working Paper ;, 2013)
Estimates of the current and future structure of employment in sub-Saharan Africa (2005-20) are obtained based on household survey estimates for 28 countries and an elasticity-type model that relates employment to economic growth and demographic outcomes. Agriculture still employs the majority of the labor force although workers are shifting slowly out of the sector. Sub-Saharan Africa's projected rapid labor force growth, combined with a low baseline level of private sector wage employment, means that even if sub-Saharan Africa realizes another decade of strong growth, the share of labor force employed in private firms is not expected to rise substantially. Governments need to undertake measures to attract private enterprises that provide wage employment, but they also need to focus on improving productivity in the traditional and informal sectors as these will continue to absorb the majority of the labor force.